2006
DOI: 10.1143/jjap.45.l673
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Demonstration of a Ring-Cavity Q-Switched Fiber Regenerative Amplifier

Abstract: The static and dynamic magnetic behaviour of Fe nanoclusters with controlled sizes in the range 140-270 atoms (1.5-1.8 nm) deposited in situ from a gas aggregation source on magnetic vitrovac amorphous ribbons has been studied using synchrotron radiation. The static magnetization of the cluster films in the exchange field of the substrates was measured as a function of coverage using magnetic linear dichroism in the angular distribution (MLDAD) of the Fe 3p core level photoemission. The switching dynamics were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Pumping above a certain threshold can lead to self-oscillation in the amplifier. This kind of regenerative amplifier can easily achieve the high repetition rate pulse regenerative amplification relative to the other kind of regenerative amplifier that has an optical switch in the amplifier like ref [13][14][15][16]. This type of regenerative amplifier technique can also be applied to the other rare-doped fiber amplifier systems such as Yb and Tm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Pumping above a certain threshold can lead to self-oscillation in the amplifier. This kind of regenerative amplifier can easily achieve the high repetition rate pulse regenerative amplification relative to the other kind of regenerative amplifier that has an optical switch in the amplifier like ref [13][14][15][16]. This type of regenerative amplifier technique can also be applied to the other rare-doped fiber amplifier systems such as Yb and Tm.…”
Section: Discussionmentioning
confidence: 99%
“…The pump power is under the self-lasing threshold. The second kind has an optical switch in the amplifier [13][14][15][16]. The usage of an optical switch provides some flexibility to amplify high-repetition-rate pulses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, all-fiber regenerative amplifiers can easily operating at saturation which can enhance the output stability a lot. In 2006, Yang [5] reported a ring cavity, Q-switched fiber regenerative amplifier that achieved 40-dB gain and 30-nJ output pulse energy at 1 530 nm. Recently Xin et al [6] demonstrated a Yb-doped all-fiber regenerative amplifier operating at 1 053 nm amplified 10-ns, 15-pJ square pulses to 240 nJ.…”
mentioning
confidence: 99%